The Function And Role Of Village Head Leadership In Improving The Competence Of Village Apparatus - Frans Julianto Gulo; Eliagus Telaumbanua; Palindungan Lahagu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The leadership of the village head has an important role in the management and development of the village, including in improving the competence of the village apparatus. This research focuses on Fodo Village, South Gunungsitoli District, Gunungsitoli City, to explore how village heads implement leadership functions in improving the competence of village officials. Through a qualitative approach, data is collected through interviews and participatory observations. The results of the study show that village heads carry out various leadership functions, such as instructive, consultative, participatory, delegation, and control, which have a positive impact on improving the competence of village officials. Nonetheless, challenges such as lack of technical skills and low motivation are still obstacles that must be overcome. The study concludes that a combination of good leadership function and individual skill development is essential to achieving village development goals. Efforts to improve the competence of village officials must consider various factors, including more intensive training and the formation of a disciplined work culture. This research is expected to contribute to leadership development at the village level and increase the effectiveness of public services.